2021
DOI: 10.1039/d1cc01669e
|View full text |Cite
|
Sign up to set email alerts
|

Rich oxygen vacancies, mesoporous TiO2 derived from MIL-125 for highly efficient photocatalytic hydrogen evolution

Abstract: Here we report a mesoporous TiO2 with large specific surface area and rich oxygen vacancies using Ti-based MOF (MIL-125) as precursor through high-temperature annealing. Such integration of unique mesoporous structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Similarly, such a phenomenon also appears for the TiO 2 photocatalyst, which is widely used for photocatalytic hydrogen production. [10][11][12][13] Previous reports have shown that Ti 4+ on the TiO 2 surface captures the photogenerated electrons and generates the active species Ti 3+ under UV irradiation. 14,15 To balance the charge, oxygen vacancies are inevitably produced around the Ti 3+ species.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, such a phenomenon also appears for the TiO 2 photocatalyst, which is widely used for photocatalytic hydrogen production. [10][11][12][13] Previous reports have shown that Ti 4+ on the TiO 2 surface captures the photogenerated electrons and generates the active species Ti 3+ under UV irradiation. 14,15 To balance the charge, oxygen vacancies are inevitably produced around the Ti 3+ species.…”
Section: Introductionmentioning
confidence: 99%
“…There are a large number of oxygen vacancies in the fluorescent sample. 62 It is worth noting that the elements of the LM doped in the substrate are in positive oxidation states, which further confirms that the Ga, Bi, In, and Sn were doped in the substrate to form substitution impurities in the form of ions. This is consistent with our study above.…”
Section: Resultsmentioning
confidence: 53%
“…Under the irradiation, electron–hole pairs are generated in the sample. The reaction process is as follows: 27 H 2 O + h + → ˙OH + H + CH 3 OH + ˙OH → ˙CH 2 OH + H 2 OCH 2 OH → HCHO + H + + e − 2H + + 2e − → H 2 After separation of the electro–hole pairs, electrons (e − ) flow out in the conduction band to reduce the H + (step (e)). The holes (h + ) help with the generation of H + and oxidize the sacrificial agent (CH 3 OH) into HCHO.…”
Section: Resultsmentioning
confidence: 99%
“…Under the irradiation, electron-hole pairs are generated in the sample. The reaction process is as follows: 27 photocatalyst…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%